HUBUNGAN STRES DENGAN EMOTIONAL EATING PADA REMAJA - Piloto, Thesya Claudya Putri; Nugraheni, Fitriana (Jurusan Gizi Politeknik Kesehatan Gorontalo, 2025)
Adolescence is a vulnerable period for experiencing stress, which can influence eating behavior, particularly emotional eating. Emotional eating refers to an individual's tendency to consume food in response to emotions, both negative and positive. This study aims to analyze the relationship between stress and emotional eating among adolescents at SMAN 5 Surabaya. This research employs a cross-sectional design with a sample of 142 students from grades X and XI, selected using the cluster random sampling technique. Stress levels were measured using the Perceived Stress Scale (PSS)-10 questionnaire, while emotional eating was assessed using the Salzburg Emotional eating Scale (SEES) questionnaire. Data analysis was conducted using the Spearman Rank test. The majority of respondents had a moderate level of stress (78.2%) and a low level of emotional eating (69.7%). The analysis results indicate a significant relationship between stress and emotional eating (p-value = 0.000) with a correlation coefficient (r = -0.290), indicating a weak negative correlation. Most respondents experienced emotional under-eating, where they tended to reduce food intake when experiencing stress. The conclusion drawn is that there is a significant relationship between stress and emotional eating among adolescents at SMAN 5 Surabaya, with a tendency toward emotional under-eating. Effective stress management is necessary to prevent negative impacts on adolescents' eating patterns.